Development of Arabic Culture-Based Storytelling Media through a Project-Based Learning Approach - Liazi Maulidi; Ratna Komalasari; Ardia Pramesti Regita Cahyani; Fathul Maujud (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This research was conducted descriptively to identify gaps, synthesize relevant concepts, and formulate the most appropriate theoretical model. The study produced a Project-Based Learning (PjBL) framework for creating Arabic culture–based storytelling that is ready to be implemented in the classroom. This model is designed to encourage students to collaborate actively and use Arabic in authentic contexts—namely by creating and presenting stories—so it is expected to enhance their speaking skills (mahārat al-kalām). In addition, the model is anticipated to increase students’ learning motivation and their understanding of Arab culture. Conceptually, this model is feasible to apply and has the potential to become an effective new approach to making Arabic language instruction more engaging and practical.The implications of this study indicate that the developed framework can serve as a guideline for teachers in designing more contextual and creative project-based Arabic language learning. Implementing this model has the potential to promote cultural integration in language teaching, improve the quality of communicative interaction in the classroom, and strengthen performance-based learning. Furthermore, this research opens opportunities for the development of media, assessments, and curricula that support Arabic cultural storytelling across different educational levels.